The maintenance of rails is a minor factor contributing to the extension of the service life of the railway track (Международный научный журнал «Инженер», 2026)
This article discusses the defects that arise in rails, which are one of the main components of railwayinfrastructure, and their current maintenance. All measures related to the maintenance of railways areprimarily aimed at improving the interaction between the rolling stock and the track. Irregularities in thetrack cause vertical and horizontal dynamic forces, which in turn increase the impact transmitted fromthe vehicle to the track and lead to the accumulation of residual deformations. This necessitates regularcorrection of the track in both the longitudinal and transverse profiles.In this regard, studying the railsand their operating conditions is considered a highly relevant issue. Today, many innovations andopportunities are being introduced in the transport sector of our country. Therefore, conducting scientificresearch using modern methodologies and reliable scientific foundations is highly appropriate.Thisarticle presents the scientific basis for the maintenance methods of rail defects.